The Bedside Guardian 2014 - Edited By Becky Gardiner (London Guardian Books, 2014)
GIFT BOOKS. 2014 will be remembered as one of the most extraordinary in the Guardian's history as the paper scooped a host of awards including the Pulitzer Prize. What is the secret of its success? Quite simply, from its hard-hitting investigations to its razor-sharp political sketches, its outspoken opinion pieces to its insightful sports coverage, the Guardian provides a platform for some of the finest reporters and commentators in the business. But, as regular readers of the paper will know, the Guardian is as much loved for its quirky wit, wilful contrariness and lively impertinence as it is for its heavyweight journalism. Here then, The Bedside Guardian brings together all the best pieces from the previous year - both intellectually challenging and unashamedly frivolous - in a comprehensive collection as eclectic and addictive as the paper itself.
Include Illustrations and Index
Keywords: World politics